Ni-Cu matrix composite reinforced with CNTs: preparation, characterization, wear and corrosion behavior, inhibitory effects - Ferdosi Heragh, Morteza; Eskandarinezhad, Sara; Dehghan, Alireza (Journal of Composites and Compounds, 2020)
St37 steel has been used in various industries due to its abundance and low cost. However, the high corrosion rate of steel in acidic environments is one of the limiting factors for its application. In this study, Ni-Cu compos-ite coating reinforced with CNTs was applied on the st37 steel substrate. The extract of the Sarang Semut plant was added to the coating as inhibitory particles and the electrochemical behavior of the coating was investigated. The X-ray diffraction test was performed for phase analysis. Hardness, wear, and dynamic potential polarization tests were performed. Results showed that the presence of CNT particles improved the hardness, tribological performance, and electrochemical behavior of the coating. Also, the presence of Sarang Semut particles acted as a barrier and protected the surface of st37 steel from corrosion. It should be noted that these particles affected the kinetics and thermodynamics of corrosion reactions and were not involved in the reactions.